2011
DOI: 10.1371/journal.pone.0025732
|View full text |Cite
|
Sign up to set email alerts
|

Colossal Aggregations of Giant Alien Freshwater Fish as a Potential Biogeochemical Hotspot

Abstract: The ubiquity and fascinating nature of animal aggregations are widely recognised. We report here consistent and previously undocumented occurences of aggregations of a giant alien freshwater fish, the Wels catfish (Silurus glanis). Aggregative groups were on average composed of 25 (±10 SD, ranging from 15 to 44) adults with estimated average total biomass of 651 kg (386 – 1132) and biomass density of 23 kg m−2 (14 – 40). Aggregations always occurred within the same location. No foraging, reproductive or anti-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…In conclusion, these findings suggest that this new predation behavior might represent an extreme example of the ability of introduced species to adapt to a new environment that could have unexpected implications for consumer-resources dynamics and ecosystem functioning [27], [28] that deserve further investigations.…”
Section: Discussionmentioning
confidence: 82%
“…In conclusion, these findings suggest that this new predation behavior might represent an extreme example of the ability of introduced species to adapt to a new environment that could have unexpected implications for consumer-resources dynamics and ecosystem functioning [27], [28] that deserve further investigations.…”
Section: Discussionmentioning
confidence: 82%
“…This behaviour was forced by DO conditions in the beginning, but the fish stayed aggregated even after the DO deficiency disappeared and DO rose up to 4.0 mg·L −1 . A large aggregation of fish brings many additional aspects, including the formation of biogeochemical hotspots (places where nutrient release by animals exceeds the need of primary producers) (Boulêtreau et al, 2011) or facilitation of spread of disease (Arneberg et al, 1998;Ogut et al, 2005). We hypothesise that the reason why the fish stayed aggregated and why they did not move back to their previous HR is connected to low temperature, which could inhibit the activity of fish.…”
Section: Id -Identification Number Of Individualmentioning
confidence: 96%
“…Nevertheless, some information regarding the aggregation of adult European catfish in a very restricted area does exist. Boulêtreau et al (2011) observed such a phenomenon in the Rhone River, but the cause of their behaviour was unclear, and no juveniles participated. Recently, some temporary catfish aggregations connected to their predatory behaviour have also been observed (Cucherousset et al, 2012).…”
Section: Id -Identification Number Of Individualmentioning
confidence: 99%
“…Similarly, the creation and enhancement of sport fishing using non-native fishes is a well-established management technique (Hickley and Chare 2004). In France and Spain, introductions of European catfish Silurus glanis (Siluridae) now support fisheries attracting anglers from across Europe, with colossal aggregations of large individuals ([1 m in length) in some rivers (Bouletreau et al 2011). In Florida, USA, Cichla species have also been introduced for sport fishing purposes (Shafland 1995).…”
Section: Value Of Non-native Fish In Brazilmentioning
confidence: 99%